Engaging Gypsy and Traveller pupils in secondary education in Wales: tensions and dilemmas of addressing difference. Issue 1 (2nd January 2018) - Hamilton, Paula
Abstract: Despite decades of research and policy, we are still some way in the U.K. from ameliorating barriers for Gypsy and Traveller pupils. A complex set of factors exist which influence young people's engagement with secondary education. This interpretive-deductive study, which draws upon 'tensions and dilemmas of difference', presents Gypsy/Traveller learners' perceptions and those of their parents and teachers about the barriers encountered. Findings around 'intra-cultural conflict' demonstrate significant tensions between and within cultures that are profound for young people during this stage of education. Resilient, supportive mothers and strong bonds with teachers and children from the mainstream community, appeared essential in helping young people to manage criticism and resist pressure to conform to cultural norms. However, a fundamental shift in societal attitude is required and critical thought paid to inclusive education, or young learners who remain in education may end up on the periphery of both societies.